CREDIT AND HOUSING MARKETS IN VIETNAM: EVIDENCE FROM VECM ANALYSIS - Ngoc Toan Bui (Фінансово-кредитна діяльність: проблеми теорії та практики)
This study focuses on examining the role of the credit market in the housing market in the two largest cities of Vietnam, a developing country with limited empirical research on this issue. In specific, the credit market is defined by credit growth, while the housing market is measured by the house price index. The dataset is collected quarterly from Q1 2009 to Q4 2022. By employing the Vector Error Correction Model (VECM) method, the findings reveal that bank credit has a positive impact on housing prices in the long term, a result observed in both of Vietnam's largest cities - Ho Chi Minh City and Hanoi City. Moreover, economic growth and the consumer price index also significantly influence housing prices in Vietnam. Based on these findings, the author suggests implications for promoting the credit market coupled with the development of the housing market. Furthermore, the findings offer practical and meaningful insights not only for Vietnam's cities but also for other developing countries worldwide.